AN IMMUNOHISTOCHEMICAL STUDY OF COMBINED HEPATOCELLULAR AND CHOLANGIOCELLULAR CARCINOMA-ON THE SIGNIFICANCE OF MONOCLONAL ANTIBODY BER-EP4 - SUZUKI, Yasushi; NONAKA, Hiroko; HASEBE, Yukitake; NAKAZAKI, Haruhiro; TAKITA, Wataru; KOBAYASHI, Kazuo; OOSHIRO, Toru; TOKURA, Natsuki; WATANABE, Masashi; SHIMOJIMA, Yasuhiro (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2000)
Monoclonal antibody Ber-EP4 is useful for the differentiation between cells of the mesodermal and epithelial derivation. We conducted immunohistologic examinations using the antibody to Ber-EP4 and cytokeratin (subclass No.8) to study clinicopathologic findings. Subjects were eight patients with combined hepatocellular and cholangiocellular carcinoma (HCC-CCC). In the HCC-CCC, the area of cholangiocellular carcinoma (CCC) was stained strongly on cytokeratin staining compared with one of hepatocellular carcinoma (HCC). On Ber-EP4 staining, the patient, who showed posttive staining in CCC, revealed positive staining in HCC, too. Both parts had the same immunohistologic property. When clinical data such as existing hepatic impairment and viral infection in each patient are considered, it seems that the result of Ber-EP4 staining can be an indicator to guess the origin of HCC-CCC. It also seems that the result of Ber-EP4 staining is useful to consider whether the malignant tumor in the liver is primary or not.